KARAKTERISTIK PENGGUNA DAN MANAJEMEN TRANSPORTASI ANTARMODA DI WILAYAH CIREBON SELAMA PANDEMI COVID-19 - herry - hermawan; Pratikso Pratikso; Rahmat Mudiyono (LPPM Universitas Abdurrab, 2022)
The era of disruption expanded due to the Covid-19 pandemic in mid-March 2020 globally, including in the transportation sector. An investigation was conducted to identify the characteristics of users of intermodal public transportation and management of intermodal transportation in Cirebon, West Java, Indonesia. The investigative design used mixed methods. The sample with accidental sampling technique was 300 respondents, and 6 transportation experts in Cirebon City. The data were analyzed descriptively and multicriteria decision through AHP. The investigation provides information that: (1) Characteristics of respondents using intermodal transportation are 21-30 years old, male, last education D3/S1, private employee, with income less than 1.5 million per month. (2) Alternative policies that should be taken by the Cirebon City Government in overcoming traffic problems in the Cirebon area are as follows: (a) Revision of Regional Regulation No. 8 of 2016, (b) Development of Mass Transportation Systems. Policy for developing an integrated public transportation system in the form of bus rapid transit. This policy is a step to solve traffic jams that can reduce the use of private vehicles